(untitled) (mathematica didactica, 2025)
In today’s world, data plays a major role, which is why the correct handling of statistical graphs such as histograms, boxplots and dotplots is an important part of data literacy. However, systematic errors can occur when interpreting these graphs. In this article, these errors are examined in the light of conceptual change theory. It is shown that systematic errors in the interpretation of statistical graphs are based on conceptual difficulties. These can be traced back to the fact that previously learned basic concepts are not correctly adapted to new graphs.